2004
DOI: 10.1177/0266242604046298
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Consultancy Services as an Instrument for the Development of Remote SMEs

Abstract: This article claims that traditional supply of public support programmes for small and medium-sized enterprises (SMEs) in remote locations fails to achieve its objective: it is not met by 'hidden' demand. An experiment was conducted in SMEs that did not use available consultancy programmes in three remote regions in the state of Ceara in Brazil: a consultant was sent to each of them on a diagnosis mission. The results indicate that there is a 'hidden demand', in the sense that most of the enterprises need cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…On the other hand, diagnosis can change the owner-manager's perspectives. Schwartz and Bar-El (2004) show how 37 owner-managers in Brazil changed their views about their business problems after receiving free diagnostic consultancy. Those issues that increased in salience were those that were under the control of the owner-manager: the management, planning, and production in the firm.…”
Section: Business Advice Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, diagnosis can change the owner-manager's perspectives. Schwartz and Bar-El (2004) show how 37 owner-managers in Brazil changed their views about their business problems after receiving free diagnostic consultancy. Those issues that increased in salience were those that were under the control of the owner-manager: the management, planning, and production in the firm.…”
Section: Business Advice Literaturementioning
confidence: 99%
“…Mole and W. Keogh points to the role of diagnosis in stimulating the potential for change. The approach to diagnosis was unclear in Schwartz and Bar-El (2004). All approaches have their difficulties: the informal 'fireside chat' may overlook aspects of the business; the formal approach may fail to develop rapport with the client.…”
Section: Business Advice Literaturementioning
confidence: 99%
“…Public consulting services (at subsidized price) are intended to solve market failures: increased demand and economic growth through multiplier effect, decreasing inequalities and social problems, technology diffusion effects, social stability, induce social benefits far beyond the benefits of the single entrepreneur (Schwartz & Bar-El, 2004). The way for social support to be delivered effectively to entrepreneurs is to make that support tailored to their individual needs (Schwartz & Bar-El, 2004). The results of their study indicate that there is a 'hidden demand' in the sense that most enterprises need consultancy, but do not apply for the available services.…”
Section: Different Academic Papers Analysed and Investigated Differenmentioning
confidence: 99%
“…Although some developed‐country research (e.g., Sexton et al. , p. 6) suggests that small businesses often have a clear idea about what they want to learn, empirical research conducted in developing countries has revealed that many owner–managers lack a real understanding of their training needs (e.g., Schwartz and Bar‐el ; Trulsson ). The comments of owner–managers tended to suggest either that their own success implied that help was unnecessary, or that advice alone was insufficient to address current challenges:
If my management aspect is not good, I wouldn't have been able to build the most popular restaurant in this area.Although they do provide the needed advice, they do very little to support or lift us up from our problems.
…”
Section: Findings and Comparative Analysismentioning
confidence: 99%